Transition of electrochemical measurement to machine learning in the perspective of two-dimensional materials - Jitapunkul, Kulpavee; Chenwittayakhachon, Apiphu; Iamprasertkun, Pawin (Frontiers in Materials, 2022)
Two-dimensional materials (e.g. graphene, and transition metal dichalcogenides) have become ubiquitous in electrochemical contexts including energy storage, electrocatalyst, and ion-selective membranes. This is due to its superior electrochemical properties, specifically “capacitance”, which can be referred to the storage ions at the electrolyte/materials interfaces. Experimental work and computational chemistry were carried out in the past decade for solving and improving the understanding of two dimensional materials; however, these techniques are relatively expensive, complex, and time-consuming. Therefore, we accentuate the future trend of two dimensional material study with machine learning as the modest alternative. In this perspective, the intrinsic capacitance properties of the two dimension materials were described from an atomic level, explaining the heteroatom doping to a nanoscopic level, showing (basal vs. edge capacitance). The studies also extended to the macroscopic level i.e., the flake size of the two dimensional materials. We then shade more light on the applicability of machine learning coupled with the “fundamental measurement” for solving electrochemistry of two dimensional materials. The shallow artificial neural network was demonstrated for the prediction of CV curves using the data from size-dependent graphene. In addition, the application of deep neural networks with complicated architecture has also been explored through the prediction of capacitance for heteroatom-doped graphene. This perspective provides a clear background and creates the connection between fundamental measurement and machine learning for understanding the capacitance properties of two dimensional materials.